Automated Infrared Pupillometer Use in Assessing the Neurological Status in Pediatric Neurocritical Care Patients: Case Reports and Literature Review - McGetrick, Molly E.; Schneider, Nathan; Olson, DaiWai M.; Aiyagari, Venkatesh; Miles, Darryl (Journal of Child Science, 2021)
Automated infrared pupillometry (AIP) is rapidly becoming an accepted standard for the evaluation of pupil size and reactivity in adult neurocritical care. Recently, pediatric centers are increasingly utilizing this technology, but data supporting its use in children are limited. Our pediatric intensive care unit instituted AIP as a standard of care for pupillary light assessments in neurocritical care patients in early 2020. In this article, we describe four cases highlighting the advantage of using objective assessments of the pupillary light reactivity response measured by the Neurological Pupil index (NPi) to detect early changes in the patient's neurological status. These cases support the applicability of AIP in pediatric neurocritical care as a noninvasive neurologic monitoring tool. The NPi may be superior to manual pupil assessments by providing a numerical scale for accurate trending clinical status of a patient's neurologic condition.
Keywords: Pediatrics; neurocritical care; neurological monitoring; cardiac arrest; brain injury